The Impact of Motivation on Performance: The Role of Organizational Commitment - Mochammad Munir Rachman (Universitas Airlangga, 2022)
Objective: The study aims to analyze the important role of motivation in improving the performance of company employees with the support of organizational commitment as a mediation. Design/Method/Approach: This study uses a causality model with an explanatory method. The sample size of 160 respondents was obtained by distributing questionnaires to employees of a service company in Indonesia. The explanatory method as a measurement of confirmatory factor analysis and SEM analysis to test the model and significance test. Findings: The results of this study prove that motivation has a positive and significant effect on employee performance. Motivation-mediated employee success can master intrinsic factors and strengthen the associated extrinsic motivation because high-performance results are supported by affective, continuance, and normative commitment. Employee commitment, as a bond of experience, values, and beliefs, indirectly affects employee performance because it is needed to achieve organizational goals. Originality: This paper lies in a comprehensive study that combines the variables of motivation, organizational commitment, and performance into a complete study model. The originality of this paper shows the role of The Role of Motivation, How It Affects Employee Performance, and Organizational Commitment. Implications for Practice/Policy: Employee success in meeting company goals is important because employee motivation for commitment can move actions toward high performance. Furthermore, our findings show that the strength of the relationship between motivation and commitment mediates in helping the company's needs and changing employee actions that are more profound in producing job performance for the company's goals.